2017
DOI: 10.7717/peerj.4109
|View full text |Cite
|
Sign up to set email alerts
|

Formoterol attenuates increased oxidative stress and myosin protein loss in respiratory and limb muscles of cancer cachectic rats

Abstract: Muscle mass loss and wasting are characteristic features of patients with chronic conditions including cancer. Therapeutic options are still scarce. We hypothesized that cachexia-induced muscle oxidative stress may be attenuated in response to treatment with beta2-adrenoceptor-selective agonist formoterol in rats. In diaphragm and gastrocnemius of tumor-bearing rats (108 AH-130 Yoshida ascites hepatoma cells inoculated intraperitoneally) with and without treatment with formoterol (0.3 mg/kg body weight/day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 70 publications
2
29
0
Order By: Relevance
“…The Yoshida AH-130 ascites hepatoma is a suitable approach to study the underlying biological events of muscle wasting in cancer-induced cachexia, as already demonstrated in several investigations [10][11][12][26][27][28]51]. In the study, expression levels of activated NF-κB p65 and FoxO3 were significantly increased in both respiratory and limb muscles.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The Yoshida AH-130 ascites hepatoma is a suitable approach to study the underlying biological events of muscle wasting in cancer-induced cachexia, as already demonstrated in several investigations [10][11][12][26][27][28]51]. In the study, expression levels of activated NF-κB p65 and FoxO3 were significantly increased in both respiratory and limb muscles.…”
Section: Discussionmentioning
confidence: 72%
“…Protein levels of the different molecular markers analyzed in the study were explored by means of immunoblotting procedures as previously described [14][15][16][17][18]25,45,46,50,51].…”
Section: Immunoblottingmentioning
confidence: 99%
“…By contrast, a preclinical study has shown that cachexia induced in the host rat by the AH-130 tumor leads to distinct responses in locomotor and respiratory muscles, the former being more susceptible to oxidative stress than the latter, despite the increase of the endogenous antioxidant defense (115), likely due to an ineffective adaptive response. Similarly, increased pro-oxidant species coupled with the activation of the antioxidant defense has been reported in the muscle of C26-bearing mice (6,12).…”
Section: Role Of Oxidative Stress In Muscle Wasting and Dysfunctionmentioning
confidence: 91%
“…As such, in models of disuse muscle atrophy and wasting, a rise in the levels of markers of proteolysis, autophagy, apoptosis, oxidative stress, and epigenetic modifications have been shown in muscles of both patients [2,[6][7][8][9][10][11] and animals [12][13][14][16][17][18][19][20][21][22]. Additionally, alterations in the structure of the myofibers along with a reduction in their size have also been demonstrated in muscles following periods of inactivity [12][13][14][16][17][18][19][20][21][22].The study of the kinetics of the pathophysiological and biological events whereby the loss of muscle mass takes place following periods of disuse is important [23][24][25]. In this regard, the sequence of the expression of markers of proteolysis, apoptosis, autophagy, signaling, of structural alterations and fiber type switches, and that of impaired function have already been described in previous investigations [23][24][25].Post-translational modifications of transcription factors that signal proteolytic activation in muscles were described in several models of muscle atrophy [24][25][26].…”
mentioning
confidence: 99%